KINERJA KARYAWAN DI PT INDOFARMA TBK: APAKAH DIPENGARUHI OLEH RESTRUKTURISASI ORGANISASI DAN BUDAYA ORGANISASI DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING - Safita, Siti Hajar Nur; Budiantoro, Anandha (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
The condition that the company's performance is currently declining and improvements are needed, one of which is human resources. Steps to restructure the organization and implement an optimal organizational culture are the choices implemented at PT Indofarma Tbk. Organizational restructuring and employee organizational culture can influence employee performance and job satisfaction. The purpose of this research is to determine the direct influence of organizational restructuring, organizational culture and job satisfaction on employee performance as well as the direct influence of organizational restructuring and organizational culture on job satisfaction. The purpose also to determine the indirect influence of organizational restructuring and organizational culture on employee performance through job satisfaction. This is quantitative research with data obtained from research samples were analyzed according to statistical methods using SEM-PLS. The sampling technique with cluster random sampling at PT Indofarma Tbk, namely 260 respondents using a questionnaire. The research results stated hypothesis was accepted, there was a direct influence on organizational culture variables of 42.6%, job satisfaction of 21.1% on employee performance, there was a direct influence of organizational restructuring of 31.1% and organizational culture of 50.5% on job satisfaction. at PT Indofarma Tbk. However, the hypothesis was rejected with a result of 1.1%, indicating that organizational restructuring had no direct effect on employee performance at PT Indofarma Tbk. Furthermore, the hypothesis is accepted that there is an indirect influence on organizational restructuring of 6.6% and organizational culture of 10.7% on employee performance through job satisfaction at PT Indofarma Tbk.